The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0196111
|View full text |Cite
|
Sign up to set email alerts
|

Association of objectively measured physical activity and sedentary time with arterial stiffness in women with systemic lupus erythematosus with mild disease activity

Abstract: ObjectivesTo examine the association of objectively measured physical activity (PA) intensity levels and sedentary time with arterial stiffness in women with systemic lupus erythematosus (SLE) with mild disease activity and to analyze whether participants meeting the international PA guidelines have lower arterial stiffness than those not meeting the PA guidelines.MethodsThe study comprised 47 women with SLE (average age 41.2 [standard deviation 13.9]) years, with clinical and treatment stability during the 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
(59 reference statements)
4
3
1
Order By: Relevance
“…Barnes et al [40] cross-sectionally observed that participants (mainly women) with SLE who reported exercising regularly had lower central arterial stiffness than sedentary SLE subjects and similar to that of healthy individuals. By contrast, Morillas-de-Laguno et al observed a lack of association of accelerometer-based physical activity with PWV in women with SLE [19]. Our results did not evidence any significant change in arterial stiffness following 12 weeks of aerobic exercise, which might have different explanations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Barnes et al [40] cross-sectionally observed that participants (mainly women) with SLE who reported exercising regularly had lower central arterial stiffness than sedentary SLE subjects and similar to that of healthy individuals. By contrast, Morillas-de-Laguno et al observed a lack of association of accelerometer-based physical activity with PWV in women with SLE [19]. Our results did not evidence any significant change in arterial stiffness following 12 weeks of aerobic exercise, which might have different explanations.…”
Section: Discussioncontrasting
confidence: 99%
“…The American College of Sports Medicine (ACSM) highlights the need to undertake a minimum of 150 min/week (i.e., accumulated in bouts of ≥10 min) of aerobic exercise of moderate to vigorous intensity in adults [18]. In a sample of women with SLE with mild/inactive disease, we cross-sectionally observed no association between accelerometer-assessed physical activity and arterial stiffness [19], although a higher level of cardiorespiratory fitness was related to lower age-related arterial stiffness in this population [20]. Although aerobic exercise has a promising role attenuating arterial stiffness in the general population [21], its effects in women with SLE have not been previously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Our results in patients with low responsiveness to drug treatment agree with other cross-sectional studies in the general population (40% of the participants had hypertension) [32] and systemic lupus erythematosus [33]. In patients with hypertension, contradictory research findings have been described.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, no association was found between moderateto-vigorous physical activity and cf-PWV. Although many studies reported an inverse association between moderate to vigorous physical activity and cf-PWV [15,17], others have reported no association [32,33]. It is important to note, however, that our participants presented levels of moderate physical activity similar to those of other studies with patients with hypertension [19,34].…”
Section: Discussionsupporting
confidence: 66%
“…A few studies have also examined associations between sedentary behaviour and indicators of CVD, sleep, physical function, quality of life and disease activity. Specifically, two studies have revealed sedentary behaviour to be linked to higher overall CVD risk scores [ 35 ] and arterial stiffness [ 36 ] in SLE. One study has reported higher sedentary behaviour to be associated with markers of sleep dysfunction in people living with SLE [ 37 ], and in AS, higher sedentary behaviour has been observed to be related to lower physical function and quality of life [ 16 ], in addition to higher disease activity [ 38 ].…”
Section: Phase 1: Links Between Behaviour and Healthmentioning
confidence: 99%